2010
DOI: 10.1007/s10059-010-0128-6
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Profile and Function of Satb2 in Zebrafish Embryonic Development

Abstract: The present study shows the expression profile and function of the homeobox gene, satb2 during zebrafish embryonic development. Satb2 was ubiquitously expressed from the 1 cell stage to the 10-somite stage in zebrafish embryos. Satb2 showed stage-specific expression profiles such as in the pronephric duct at 24 hpf, the branchial arches at 36 hpf, and the ganglion cell layer of the retina and fins at 48 hpf. Additionally, satb2 knockdown embryos were arrested at 50-60% epiboly, and transplantation experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 32 publications
4
35
0
Order By: Relevance
“…In cell culture, immature secretory granules remove specific SNARE proteins from their cytoplasmic surface to acquire the competence to fuse with the plasma membrane [78][80]. For instance, depletion of GGA3 in neuroendocrine cells inhibits sorting of VAMP4 away from neuroendocrine secretory granules, which needs to be removed to permit vesicle fusion with the membrane [81].…”
Section: Resultsmentioning
confidence: 99%
“…In cell culture, immature secretory granules remove specific SNARE proteins from their cytoplasmic surface to acquire the competence to fuse with the plasma membrane [78][80]. For instance, depletion of GGA3 in neuroendocrine cells inhibits sorting of VAMP4 away from neuroendocrine secretory granules, which needs to be removed to permit vesicle fusion with the membrane [81].…”
Section: Resultsmentioning
confidence: 99%
“…Given the prominent role of DNM2 in cellular function and human disease, characterizing the endogenous zebrafish dynamin-2 is an important task. Several studies of zebrafish endocytosis have utilized putative markers or inhibitors of dynamin-2; however, none of these reports examined functional or structural similarity between human DNM2 and a zebrafish homolog [13], [14], [15]. Establishing this orthologous relationship will enable future studies of endocytosis and other dynamin-related pathways in the zebrafish.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this early expression, embryos injected with a satb2 MO stalled during epiboly, adopted an elongated ellipsoidal shape, and died by 13 hpf (Ahn et al, 2010). Epiboly defects in satb2-MO injected larvae were accompanied by an abnormal actin cytoskeleton and aberrant expression of markers of mesoderm (ntl) and neural plate (sox3), interpreted to reflect abnormal cellular migration (Ahn et al, 2010). Like embryos injected with dnIrf6, satb2 morphants died during gastrulation (Ahn et al, 2010).…”
Section: Satb2-associated Syndromementioning
confidence: 89%
“…Two studies reported satb2 is highly expressed in the pharyngeal arches 48 hpf (Ahn et al, ; Sheehan‐Rooney et al, ), and one that it can be detected as early as the single cell stage (Ahn et al, ). Consistent with this early expression, embryos injected with a satb2 MO stalled during epiboly, adopted an elongated ellipsoidal shape, and died by 13 hpf (Ahn et al, ).…”
Section: Use Of Zebrafish To Explore the Developmental Functions Of Gmentioning
confidence: 99%
See 1 more Smart Citation